Hyperbaric Oxygen Ameliorates Insulin Sensitivity by Increasing GLUT4 Expression in Skeletal Muscle and Stimulating UCP1 in Brown Adipose Tissue in T2DM Mice - Liu, Yuan; Zhang, Di; Yuan, Junhua; Song, Limin; Zhang, Caishun; Lin, Qian; Li, Manwen; Sheng, Zhi; Ma, Zhengye; Lv, Fengyuan; Gao, Guangkai; Dong, Jing (Frontiers in Endocrinology, 2020)
Hyperbaric oxygen therapy (HBOT) is a treatment modality useful for diseases. Hypoxia could stimulate the induction of insulin resistance. Therefore, we sought to determine whether hyperbaric oxygen (HBO) would ameliorate insulin sensitivity by promoting glucose transporter type 4 (GLUT4) expression in muscle and by stimulating UCP1 in brown adipose tissue (BAT) in a streptozocin (STZ)-induced type 2 diabetes mellitus (T2DM) mouse model. Male C57BL/6J mice were treated three times with low-dose streptozocin (60mg/kg, i.p.) and were fed with high-fat diets (HFD) to establish the T2DM model. HBO was administered daily as 100% oxygen at 2.0 atmosphere absolute (ATA) for 1 hour for a week. We found that HBO significantly reduced blood glucose levels and attenuated insulin resistance in T2DM mice. HBO modulated food intake by influencing the activity of neuropeptide Y (NPY)-positive neurons in the arcuate nucleus (Arc). Immunofluorescence showed that GLUT4 levels were increased induced by HBO in T2DM but not in HFD mice, and that phosphorylated Akt (p-Akt) and phosphorylated AMPK (p-AMPK) levels were elevated. Morphological staining of brown adipose tissue and increasing uncoupling of protein 1 (UCP1) expression demonstrated the promotion of metabolism after HBO treatment. These findings suggest that HBO ameliorates insulin sensitivity by stimulating the Akt signaling pathway, promoting GLUT4 expression in muscle and UCP1 in BAT in T2DM mice.